Hubungan Pemberian Makanan Pendamping Asi (Mp-Asi) dengan Kejadian Stunting Pada Balita Usia 24-60 Bulan Diwilayah Kerja Puskesmas Tanjung Buntung Kota Batam Tahun 2022. - Aprilya Roza Werdani; Made Tantra Wirakesuma; Siska Pratiwi; Nurul Farha; Rafika Hubby (Lembaga Pengembangan Kinerja Dosen, 2022)
In Indonesia, stunting is one of the most common diseases in toddlers with a percentage (27.67%) caused by several factors, one of which is complementary feeding. This study aims to determine the relationship between complementary feeding (MP-ASI) and the incidence of stunting in toddlers aged 24-60 months in the Tanjung Buntung Public Health Center, Batam City in 2022. The design of this study used a case control. Respondents in this study were 28 cases and 28 controls. The sampling technique used is purposive sampling. The results of the Chi-Square test show (p value = 0.001; OR = 0.133) so that Ho is rejected, this indicates a relationship between complementary feeding and the incidence of stunting in toddlers aged 24-60 months in the working area of ​​Tanjung Buntung Public Health Center, Batam City. year 2022with. It can be concluded that there is a relationship between the provision of complementary feeding with the incidence of stunting in toddlers aged 24-60 months and with an OR value of 0.133, which means that toddlers who are given inappropriate complementary foods can be at risk of stunting 0.133 times. It is hoped that health services should increase the provision of information and education to mothers of toddlers about the importance of nutrition and the correct way of processing complementary feeding needed by toddlers in an effort to prevent stunting.